Potensi Toleransi Oral Glukosa Ekstrak Biji Kedelai (Glycine max), Rimpang Jahe (Zingiber officinale) dan Kombinasinya pada Tikus Model Diabetes - Purnomo, Yudi (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2018)
ABSTRACTDiabetes mellitus (DM) is metabolic syndrome signaled by hyperglycemic chronic and it contribute to several complication risk. Soya(Glycine max) andGingger (Zingiber officinale) are used for the alternative theraphy of DM,however, the potency to regulate blood glucose level especially in it’s combination has not been evaluated.The objective of this study to investigate anti-hyperglycemic effect of Glycine max (G. max) seed extract, Zingiber officinale (Z. officinale) rhizoma and it’s combinationon diabetic rat.This study uses control group post test only with male spraque dawley rats divided into 2 control group and 3 test group (n=5 rats). Diabetic rats was induced by High Fructose and Lipid Diet (HFLD) and multiple dose streptozotocin 25 mg/kg bw (i.p).The rat was administrated orally with G. max seed extract, Z. officinale and it’s combinationin dose of 5000 mg/kb bw, 500 mg/kg bw and 5000 : 500 mg/kg bwrespectively for 4 weeks. Blood sample were collected from the tail vein at 0, 30,60 and 120 minutes after oral glucose administration and thenit were measured using a commercially glucometer. The integrated area under the postprandial glucose curves (AUCs) was calculated by the trapezoidal method.The data was analyzed using ANOVA test continued with LSD test (p < 0,05). The oral administration of G. max seed extract, Z. officinale and it’s combinationwere able to decrease blood glucose AUC about 30 %, 35 % and 35 % respectively compared to diabetic group (p<0.05). In diabetic groups, blood glucose AUC was increased approximately 1.5-fold compared to normal group (p<0.05). Single composition of Z. officinaleextract and its combination with G.maxdecrease blood glucose AUC more compared to the single composisition of G. maxseed extract after glucose stimulation. Key words : AUC, Combination, Diabetic, G. max, Z. officinale